Investigation of Blood Plasma Viral Nucleocapsid Antigen as a Marker of Active Severe Acute Respiratory Syndrome Coronavirus 2 Omicron Variant Infection - Damhorst, Gregory L; Schoof, Nils; Nguyen, Phuong-Vi; Verkerke, Hans; Wilber, Eli; McLendon, Kaleb; O’Sick, William; Baugh, Tyler; Cheedarla, Suneethamma; Cheedarla, Narayanaiah; Stittleburg, Victoria; Fitts, Eric C; et al. (Open forum infectious diseases, 2023)
Abstract Background Nasopharyngeal qualitative reverse-transcription polymerase chain reaction (RT-PCR) is the gold standard for diagnosis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, but it is not practical or sufficient in every clinical scenario due to its inability to distinguish active from resolved infection. Alternative or adjunct testing may be needed to guide isolation precautions and treatment in patients admitted to the hospital. Methods We performed a single-center, retrospective analysis of residual clinical specimens and medical record data to examine blood plasma nucleocapsid antigen as a candidate biomarker of active SARS-CoV-2. Adult patients admitted to the hospital or presenting to the emergency department with SARS-CoV-2 ribonucleic acid (RNA) detected by RT-PCR from a nasopharyngeal swab specimen were included. Both nasopharyngeal swab and a paired whole blood sample were required to be available for analysis. Results Fifty-four patients were included. Eight patients had positive nasopharyngeal swab virus cultures, 7 of whom (87.5%) had concurrent antigenemia. Nineteen (79.2%) of 24 patients with detectable subgenomic RNA and 20 (80.0%) of 25 patients with N2 RT-PCR cycle threshold ≤ 33 had antigenemia. Conclusions Most individuals with active SARS-CoV-2 infection are likely to have concurrent antigenemia, but there may be some individuals with active infection in whom antigenemia is not detectable. The potential for high sensitivity and convenience of a blood test prompts interest in further investigation as a screening tool to reduce reliance on nasopharyngeal swab sampling and as an adjunct diagnostic test to aid in clinical decision making during the period after acute coronavirus disease 2019.